Ultrastructural analysis of human umbilical cord derived MSCs at undifferentiated stage and during osteogenic and adipogenic differentiation. (4th May 2018) - Ozkan, Serbay; Isildar, Basak; Oncul, Mahmut; Baslar, Zafer; Kaleli, Semih; Koyuturk, Meral
ABSTRACT: Mesenchymal stem cells (MSCs) are considered as an important tool for regenerative medicine and experimental treatments. Unveiling the ultrastructural changes during the differentiation of MSCs might help us to understand the nature of the process and to develop novel therapeutic approaches. For this purpose, human umbilical cord (hUC) was chosen as MSC source. In the first place, MSCs were isolated from sub-amniotic, intervascular and perivascular areas of hUC by enzymatic and tissue explant method to determine the most favorable region of hUC and technique for further processing. Therefore, microscopic and growth kinetics analyses showed that there was no clear difference in the morphologies and proliferation rates among the hUC-MSC groups. Flow cytometric analysis showed that CD44 and CD90 MSC markers were highly expressed, while CD34 and CD45 hematopoietic stem cells markers were expressed at low degree. Because our preliminary results showed that there was no conspicuous superiority among the hUC-MSCs groups, whole UC was utilized as a source, and tissue explant method was applied to isolate MSCs for further differentiation analysis. At the 1 st and 3 rd week of osteogenic and adipogenic differentiation, ultrastructural analysis showed an increase in the number of secondary lysosomes in comparison with the undifferentiated status. Increase in the mitochondrial content was also detected at the 1 st week of adipogenic differentiation. Consequently, ultrastructural changes including increase in the number of mitochondria and secondary lysosomes during the adipogenic and osteogenic differentiation could be attributed to the switch in energy metabolism of the MSCs and increment in the lysosomal activity respectively.